Structure, conduct and performance of maize markets in Malawi - Ochieng, Dennis O.; Botha, Rosemary; Baulch, Bob (International Food Policy Research Institute, 2019)
Seasonal analysis of the structure, conduct, and performance (SCP) of markets for staple crops has received relatively little attention in food policy analysis yet it has important implications for food and nutrition security. This study employs a mixed methods approach to analyze the SCP of maize markets in Malawi in the 2018/19 main harvest and lean seasons. We interviewed 749 traders from 74 markets across 8 districts, held 28 focus group discussions (FGD) with a total of 480 farmers and analyzed daily and weekly price data from 13 regional markets. The structure of maize markets was explored by examining marketing channels, barriers to entry and the competitiveness of different tiers of the marketing chain. Inequality in sales revenues, switches in trader types between seasons, quality and weights standardization, and the behavior of traders were used to examine market conduct. Performance was assessed by examining traders’ costs and margins, and the spatial and temporal integration of maize markets. We find that Malawi’s maize market is pyramidal in structure and highly competitive at lower tiers of trade but ‘oligopolistic’ at higher tiers. The market channels vary across seasons with switches between trader types and instances of rural-urban trade reversals. There is considerable inequality of sales revenues among traders of similar capacities, and a widespread lack of structured trading despite existing institutions. A high ratio of marketing costs to revenue suggests marketing inefficiencies. Malawi maize prices were highly seasonal and more volatile than neighboring countries. In contrast to previous studies, our findings show weak spatial integration of markets and slow price adjustments to long-run equilibrium values even among short-distance market pairs. The study highlights five pathways to improving Malawi’s maize marketing system: (1) increased policy predictability to promote private-sector investment; (2) institutionalization of quality grades and standardization of weights and measures; (3) increased commercialization of smallholder maize production; (4) investment in enabling infrastructure; and (5) the promotion of structured trading.